Statins in Non-alcoholic Steatohepatitis - Torres-Peña, Jose D.; Martín-Piedra, Laura; Fuentes-Jiménez, Francisco (Frontiers in Cardiovascular Medicine, 2021)
Non-alcoholic fatty liver disease (NAFLD) is the first cause of chronic liver disease worldwide. The spectrum is broad from hepatocellular carcinoma, cirrhosis, fibrosis, fatty liver, non-alcoholic steatohepatitis (NASH). NASH is a condition associated with the metabolic syndrome, overweight, obesity, dyslipidemia and type 2 diabetes mellitus. It is a dynamic condition that can regress to isolated steatosis or progress to fibrosis and cirrhosis. Statins exert anti-inflammatory, proapoptotic, and antifibrotic effects. It´s has been proposed that this drugs could have a relevant role in NASH. In this review we provide an overview of current evidence, from mechanisms of statins involved in the modulation of NASH to human trials about the use of statins to treat or attenuate NASH.